Split body: Extending self-location by splitting a body left and right - Kondo, Ryota; Sugimoto, Maki (Frontiers in Virtual Reality, 2022)
Is it possible to feel part of one’s own body even when the body part is separated from the body? If so, we could exist in different locations by splitting the self-body and using our body in each location. In a study in which the illusion that two bodies are one's own body was induced using virtual reality (VR), the participants felt as if they were at two locations through the two bodies. However, this illusion was weak and reported only subjectively. We hypothesized that this was because two presented bodies moved synchronously with one participant's movement or the simultaneous stroking of one participant's body and two presented bodies switched their attention and weakened body ownership. In this study, we investigated whether splitting one body into left and right in VR could induce body ownership and extend the self-location while maintaining a one-to-one correspondence between the participant’s body and the presented body. The results showed that weaker body ownership was induced in the split body than in the normal body and the self-location was extended to the right side of the body. The participants did not report a sense of having more than one body but reported a sense of body spreading, suggesting that the split bodies were perceived as a single body extending to the right side.